Implementation of Digital Marketing and Simple Financial Reports on MSMEs in Bojong Koneng Village - Chandra Ayu Pramestidewi; Samsuri; Erny Amriani Asmin; Rakha Prabu Alamsyah; Rizky Algafiky; Tiara Axchellawati; Lia Fitriani Masriya; Siti Hajar Sulaeman Putri; Muhammad Samsul Rizal; An Alawiyah; Ghea Nurhalimatuzzahroh (Jurnal Pengabdian Masyarakat Formosa, 2023)
In Bojong Koneng Village, District. Babakan Madang, Djuanda University Bogor held outreach to MSME players. MSMEs in Bojong Koneng Village often experience the same problems: financial management, promotional tools and digital marketing. Therefore, training is needed in financial management and digital marketing as well as training to expand the product market with banners. By implementing and developing digital marketing, Bojong Koneng Village MSMEs will benefit. It is hoped that Bojong Koneng Village MSMEs will understand and apply the results of this training, especially regarding financial management, which will teach them accounting process skills. They will also be able to apply digital marketing practices in their daily business, so they can develop their business and increase income.